A 10-year time-series analysis of respiratory and cardiovascular morbidity in Nicosia, Cyprus: The effect of short-term changes in air pollution and dust storms, 1994-2004 - Middleton, Nicos; Yiallouros, Panayiotis K.; Kleanthous, Savvas; Kolokotroni, Ourania; Schwartz, Joel D.; Dockery, Douglas W.; Demokritou, Philip; Koutrakis, Petros (My University, 2008)
Background: To date, a substantial body of research has shown adverse health effects of short-term changes in levels of air pollution. Such associations have not been investigated in smaller size cities in the Eastern Mediterranean. A particular feature in the region is dust blown from the Sahara a few times a year resulting in extreme PM10 concentrations. It is not entirely clear whether such natural phenomena pose the same risks. Methods: The effect of changes in daily levels of particulate matter (PM10) and ozone (O3) on hospitalization for all, cardiovascular and respiratory causes in the two hospitals in Nicosia during 1 January 1995 and 30 December 2004 was investigated using generalized additive Poisson models after controlling for long- and short-term patterns as well as for the effect of weather. Meteorological records were reviewed to identify dust-storm days and analyses were repeated to quantify their effect on cardio-respiratory morbidity. Results: For every 10 μg/m3 increase in daily average PM10 concentrations, there was a 0.9% (95%CI: 0.6%, 1.2%) increase in all-cause and 1.2% (95%CI: -0.0%, 2.4%) increase in cardiovascular admissions. With respect to respiratory causes, an effect was observed only in the warm months. No lagged effects with levels of PM10 were observed. In contrast, positive associations with levels of ozone were only observed the two days prior to admission. These appeared stronger for cardiovascular causes and independent of the effect of PM. All-cause and cardiovascular admissions were 4.8% (95%CI: 0.7%, 9.0%) and 10.4% (95%CI: -4.7%, 27.9%) higher on dust storm days respectively. In both cases the magnitude of effect was comparable to that seen on the quartile of non-storm days with the highest levels of PM10. Conclusion: We observed an increased risk of hospitalization at elevated levels of particulate matter and ozone generally consistent with the magnitude seen across several European cities. We also observed an increased risk of hospitalization on dust storm days, particularly for cardiovascular causes. While inference from these associations is limited due to the small number of dust storm days in the study period, it would appear imperative to issue health warnings for these natural events, particularly directed towards vulnerable population groups.
Keywords: Air pollution; Time-series; Respiratory; Cardiovascular; Hospital admissions; Dust storms